Effect of Textile Factory effluents upon concentrations of Some Trace Elements in Water of the Euphrates River at the center of Al-Nasiriyah city Southern Iraq (University of Thi-Qar Journal of Science, 2015)
The present study deal with the effect of the effluents from of Textile Factory, in concentrations of six traceelements ( Cadmium, copper, Nickel, Lead, Zinc, and Manganese) in water of Euphrates river at the center of Al-Nasiriyah south of Iraq. Five stations have been chosen, two of them where are located at the Textile Factory in AL-Nasiriyah, and three of these are located at the Euphrates river at the city center. That that samples were collected monthly as triplicates from each station and expressed seasonally, for the period from Autumn 2013 until Summer of 2014 . Trace elements are extracted by a standard method and measured by using flamed atomic absorption spectrophotometer . The mean of total concentration were ( Cadmium, Copper, Nickel, Lead, Zinc, and Magnesium) in the dissolved phase of water were (2.60, 1.88, 6.32, 13.15, 13.87, 13.30) µg / L , respectively. But its concentration in the suspended phase in water were ( 21.13 , 52.31, 1222.67, 947.12, 1298.32, 269.30) µg / gm dry weight, respectively.This study shows up that Zinc elements was in more than concentration of there trace elements under study in the dissolved and suspended phases of the studied stations. But , it is found under the permitted limits according to the international and Iraqi limitations, while the lead in dissolved phase more than the permitted limitation according to the Iraqi qualifications No(417) in 2001 and internationally according the World Health Organization in (1996 and 2006) and the Canadian Limitations in 2003.